The extracellular matrix proteins type I collagen, type III collagen, fibronectin, and laminin 421 stimulate migration of cancer cells - Graf, Fabian; Horn, Patrick; Ho, Anthony Dick; Boutros, Michael; Maercker, Christian (The FASEB journal, 2021)
For metastasis formation, individual cells from a primary tumor must migrate toward other tissues. The aim of this study was to determine if mesenchymal stromal cells (MSCs) from human bone marrow are able to emit signals that induce this migratory activity in cancer cells. We separated the supernatant of MSCs derived from human bone marrow by size-exclusion and ion-exchange chromatography and have subsequently studied the migratory behavior of the prostate cancer cell line PC3 and the breast cancer cell line MDA-MB-231 toward the respective fractions in a transwell migration assay. We identified the extracellular matrix (ECM) proteins type I collagen, type III collagen, fibronectin, and laminin 421 as potential drivers of cancer cell migration. These results could be reproduced using the corresponding isolated or recombinant ECM proteins. Knockdown of the gene encoding beta 1 integrin, an important cell surface receptor for fibronectin, has led to inhibition of cancer cell migration. This supports the hypothesis that beta 1 integrin signaling represents an initial event that leads to metastasis, and that signaling is triggered by binding of integrin heterodimers to ECM molecules. Further characterization of signaling factors and their respective receptors will have implications for anticancer drug development.